Visual Participatory Analysis: A Qualitative Method for Engaging Participants in Interpreting the Results of Randomized Controlled Trials of Health Interventions. (January 2021) - Mannell, Jenevieve; Davis, Katy; Akter, Kohenour; Jennings, Hannah; Morrison, Joanna; Kuddus, Abul; Fottrell, Edward
This article contributes to the field of mixed methods by introducing a new method for eliciting participant perspectives of the quantitative results of randomized controlled trials. Participants are rarely asked to interpret trial results, obscuring potentially valuable information about why a trial either succeeds or fails. We introduce a unique method called visual participatory analysis and discuss the insights gained in its use as part of a trial to prevent risk and reduce the prevalence of diabetes in Bangladesh. Findings highlight benefits such as elucidating contextualized explanations for null results and identifying causal mechanisms, as well as challenges around communicating randomized controlled trial methodologies to lay audiences. We conclude that visual participatory analysis is a valuable method to use after a trial.